Retinal arterial–venous pulse delay: a new specific marker for a carotid–cavernous fistula - Linton, Edward F.; Tedeschi, Thomas R.; Ahmad, Noor-Us-Sabah; Wang, Jui-Kai; Kardon, Randy H. (Frontiers in Ophthalmology, 2023)
Purpose The purpose of the study was to describe ocular blood flow changes in eyes affected by a carotid–cavernous fistula (CCF) using laser speckle flowgraphy. We hypothesized that imaging blood flow velocity waveforms in the retinal arterioles and venules simultaneously would reveal specific characteristics of an arteriovenous (AV) connection. Design The study was an observational case series, with a retrospective case–control analysis. Methods Five patients with a CCF underwent measurement of ocular blood flow using laser speckle flowgraphy. The blood flow was compared retrospectively between a control group of healthy subjects (n = 32) and patients with an elevated intraocular pressure or venous outflow impairment without an AV fistula (n = 40). The outcomes were derived from the arteriole and venule blood flow velocity waveforms, including an A–V phase delay and flow pulsatility. Results The presence of an active CCF was associated with an increased delay in the peak velocity measured in the retinal venule (10.7% ± 2.2% of the cardiac cycle duration) compared with unaffected fellow eyes (1.8% ± 0.2%; p = 0.05) or control eyes of normal subjects (2.7% ± 0.3%; p = 0.02). This delay disappeared after fistula thrombosis and was not present in eyes with a central retinal vein occlusion (CRVO), glaucoma, non-arteritic anterior ischemic optic neuropathy (NAION), or papilledema. The venule blood flow velocity decreased during systole (and in some cases momentarily stopped), leading to a delayed pulse with a greater amplitude in the venules than in fellow eyes and normal controls after normalizing to the arteriole amplitude (1.71 ± 0.3 vs 0.54 ± 0.03 vs 0.59 ± 0.02; p = 8.0E-12). This specific AV delay could also be identified in a scanning laser ophthalmoscope (SLO; SPECTRALIS®) video. Conclusion Laser speckle flowgraphy reveals dynamic retinal vascular changes in eyes affected by a CCF, which are not present in healthy controls or patients with other eye conditions, and which reverses with treatment.